2013
DOI: 10.1037/a0031335
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory and higher order factor analysis of the WJ-III full test battery: A school-aged analysis.

Abstract: Development of the Woodcock-Johnson (3rd ed.; WJ-III; Woodcock, McGrew & Mather, 2001a) was guided in part by Carroll's (1993) 3-stratum theory of cognitive abilities and based on confirmatory factor analysis (CFA), even though Carroll used exploratory factor analysis (EFA) to derive his theory. Using CFA, McGrew and Woodcock (2001) found a 9-factor model across all age ranges. To determine if the 9-factor structure holds for the full WJ-III battery, we applied currently recognized best practices in EFA to 2 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
73
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(92 citation statements)
references
References 89 publications
(182 reference statements)
16
73
1
2
Order By: Relevance
“…Three independent WISC -IV studies (Bodin, Pardini, Burns, & Stevens, 2009;Watkins, 2006;Watkins, Wilson, Kotz, Carbone, & Babula, 2006) examined the higher-order structure of the WISC -IV and found that the majority of subtest variance was associated with the higher-order general intelligence dimension and substantially smaller amounts of variance were related to the first-order factors. This is a consistent finding among Wechsler scales, specifically, as also observed with the French WISC -IV (Golay, Reverte, Rossier, Favez, & Lecerf, 2012), the French Wechsler Adult Intelligence Scale -Third Edition (WAIS -III; Golay & Lecerf, 2011), and the Wechsler Adult Intelligence Scale-Fourth Edition (WAIS -IV; Canivez & Watkins, 2010a, 2010b, as well as intelligence tests, in general (Canivez, 2008(Canivez, , 2011Canivez, Konold, Collins, & Wilson, 2009;Dombrowski & Watkins, 2013;Dombrowski, Watkins, & Brogan, 2009;Nelson & Canivez, 2012, Nelson, Canivez, Lindstrom, & Hatt, 2007.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…Three independent WISC -IV studies (Bodin, Pardini, Burns, & Stevens, 2009;Watkins, 2006;Watkins, Wilson, Kotz, Carbone, & Babula, 2006) examined the higher-order structure of the WISC -IV and found that the majority of subtest variance was associated with the higher-order general intelligence dimension and substantially smaller amounts of variance were related to the first-order factors. This is a consistent finding among Wechsler scales, specifically, as also observed with the French WISC -IV (Golay, Reverte, Rossier, Favez, & Lecerf, 2012), the French Wechsler Adult Intelligence Scale -Third Edition (WAIS -III; Golay & Lecerf, 2011), and the Wechsler Adult Intelligence Scale-Fourth Edition (WAIS -IV; Canivez & Watkins, 2010a, 2010b, as well as intelligence tests, in general (Canivez, 2008(Canivez, , 2011Canivez, Konold, Collins, & Wilson, 2009;Dombrowski & Watkins, 2013;Dombrowski, Watkins, & Brogan, 2009;Nelson & Canivez, 2012, Nelson, Canivez, Lindstrom, & Hatt, 2007.…”
supporting
confidence: 70%
“…CONSTRUCT VALIDITY OF THE WISC-IV UK et al, 2009;Watkins, 2006;Watkins et al, 2006), French WISC-IV (Golay et al, 2012), Stanford-Binet Intelligence Scales-Fifth Edition (Roid, 2003; see also Canivez, 2008), Wechsler Abbreviated Scale of Intelligence (Psychological Corporation, 1999) and Wide Range Intelligence Test (Glutting, Adams, & Sheslow, 2000; see also Canivez et al, 2009), Reynolds Intellectual Assessment Scales (Reynolds & Kamphaus, 2003; see also Dombrowski et al, 2009;Nelson & Canivez, 2012;Nelson et al, 2007), Cognitive Assessment System (Naglieri & Das, 1997; see also Canivez, 2011), French WAIS-III (Golay & Lecerf, 2011), WAIS-IV (Canivez & Watkins, 2010a, 2010bNiileksela et al, 2012), and the Woodcock-Johnson-Third Edition Psychoeducational Battery (Woodcock, McGrew, & Mather, 2001; see also Dombrowski & Watkins, 2013). The implication of these consistent findings is that the overall, omnibus FSIQ score should retain primary interpretive weight, rather than the firstorder, specific, factor-based index scores.…”
mentioning
confidence: 97%
“…More importantly, the predictive effects associated with broad and narrow dimensions as a whole were manifestly weaker once the effects of the GIA were accounted for. Given the WJ III structural validity findings furnished by Dombrowski (2013Dombrowski ( , 2014 and Dombrowski and Watkins (2013) indicating that these measures mostly sample general intelligence, the latter finding was not surprising.…”
Section: Discussionmentioning
confidence: 95%
“…Subsequent structural and latent variable modeling studies conducted on the WJ III COG suggest that (a) many of the broad and narrow ability scores contain large portions of variance attributable to g (Dombrowski, 2013(Dombrowski, , 2014Dombrowski & Watkins, 2013), (b) g exerts strong direct or indirect influence on reading achievement (Benson, 2007;Floyd et al, 2007;Floyd et al, 2012;Vanderwood, McGrew, Flanagan, & Keith, 2002), and (c) when the predictive effects g are controlled for, the aggregate incremental contributions of broad and narrow abilities may be small McGill & Busse, 2015). As a consequence, the present study sought to reexamine the findings produced by Evans and colleagues (2001) utilizing an alternative analytical scheme (HMRA) to determine the extent to which WJ III COG broad and narrow cluster scores provided meaningful improvements in the prediction of WJ III ACH reading scores beyond the GIA composite across the same age range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation